Intracerebral bleeding in patients on antithrombotic agents - Veltkamp, Roland; Rizos, Timolaos; Horstmann, Solveig (Seminars in thrombosis and hemostasis, 2013)
Patients treated with oral anticoagulants (OAC) carry a 7- to 10-fold higher risk of intracerebral hemorrhage (ICH) than patients without OAC. ICH related to oral anticoagulation (OAC-ICH) is a particularly severe form of stroke. The overall incidence of OAC-ICH ranges between 2 and 9 per 100,000 population/year and is expected to increase as the number of patients treated with OAC rises. Besides common risk factors of ICH such as age and hypertension, the intensity of anticoagulation, previous ischemic stroke, and the presence of cerebral vasculopathies (e.g., amyloid angiopathy, subcortical hypertensive arteriopathy) are associated with a greater risk of OAC-ICH. Mortality rates in OAC-ICH of 52 to 67% considerably exceed those of ICH in nonanticoagulated patients. Factors that mediate worse outcome in OAC-ICH are more frequent and prolonged secondary hematoma enlargement and intraventricular hemorrhage, The current concept of emergency treatment in OAC-ICH is rapid restoration of effective coagulation using hemostatic factors such as prothrombin complex concentrate, fresh frozen plasma, factor IX concentrates, and recombinant factor VIIa in addition to vitamin K. Emergency management of ICH under treatment with the new direct OAC is a major challenge. In the absence of specific antidotes, prothrombin concentrates are recommended mainly on the basis of preclinical data.
Gesehen am 24.02.2022